Transforming growth factor-alpha and nonsyndromic cleft lip with or without palate or cleft palate only in Kelantan, Malaysia - Rahman, R.A.; Ahmad, A.; Rahman, Z.A.A.; Mokhtar, K.I.; Lah, N.A.S.N.; Zilfalil, B.A.; Samsudin, A.R. (2008)
Objective: To determine the frequency of the transforming growth factor-alpha (TGFα) Taq1 polymorphism in nonsyndromic cleft lip with or without cleft palate (CL±P) and cleft palate only (CP) in Kelantan, Malaysia. Setting: The study was conducted at the Combined Cleft Clinic and at the Human Genome Centre in Hospital Universiti Sains Malaysia in Kelantan, Malaysia. Design: We examined the C2/Taq1 variant of the TGFα gene in 46 patients with nonsyndromic CL±P or CP only and in 33 controls. The TGFα genotype frequencies in patients were compared with those in controls using the chisquare or Fisher exact test. DNA samples were obtained from peripheral blood. Results: No association was found between TGFαTaq1 polymorphism and CL±P or CP in this case-control study. In addition, no homozygosity for the rare allele C2 was noted in CL±P, CP, or the controls. Conclusion: No evidence of TGFαTaq1 polymorphism was observed in association with CL±P and CP in this study.